Factores asociados a la aptitud cardiorrespiratoria de los escolares - Coledam, Diogo Henrique Constantino; Ferraiol, Philippe Fanelli; Dos-Santos, Júlio Wilson [UNESP]; de Oliveira, Arli Ramos (FapUNIFESP (SciELO), 2016)
Introduction: There is a high prevalence of youth that not meet the health criterion for cardiorespiratory fitness, which exposes them to risks related to metabolic, cardiovascular and mental health. Thus, it is relevant to investigate which aspects are associated with cardiorespiratory fitness in youth. Objective: To analyze the factors associated with cardiorespiratory fitness in school students. Methods: Cross-sectional study involving 736 students (50.1% female) with age between 10 and 18 years. The following has been analyzed: the socioeconomic condition, paternal education, number of siblings, physical activity perception, moderate to vigorous physical activity, participation in physical education classes, sport practice, place to practice, active transport and sedentary behavior. Height and body mass were measured and a cardiorespiratory fitness test was performed. Prevalence ratio (PR) and 95% confidence intervals were estimated using the Poisson regression. Results: For students aged less than 14 years, variables that presented association with cardiorespiratory fitness were female sex (PR = 0.79, 0.68-0.91), overweight (PR = 0.73, 0.61-0.89), physical activity perception equal to persons of the same age (PR = 1.26, 1.03-1.53), weekly physical activity 3-6h (PR = 1.21,1.05-1.38), participation in physical education classes (PR = 1.35,1.03-1.76), and sedentary behavior > 2h (RP = 0.82,0.73-0.94). With respect to students aged 14 years or more, female sex (PR = 0.35,0.19-0.63), overweight (PR = 0.25,0.09-0.66), practicing sports a few times (PR = 1.96,1.00-3.81) and frequently (PR =2.09,1.01-4.31) presented association with cardiorespiratory fitness. Conclusion: Intervention programs aiming at increasing health criterion requirement for cardiorespiratory fitness of students should promote moderate to vigorous physical activity, sport practice, participation in physical education classes and overweight reduction.
Fatores associados à aptidão cardiorrespiratória de escolares
Factors associated with cardiorespiratory fitness in school students
Keywords: Adolescent; Motor activity; Overweigh; Physical education and training; Physical fitness